2006
DOI: 10.1002/art.21748
|View full text |Cite
|
Sign up to set email alerts
|

The complex nature of the interaction between disease activity and therapy on the lipid profile in patients with pediatric systemic lupus erythematosus

Abstract: Objective. To determine the prevalence of lipid abnormalities at different times and to determine the influence of both the disease and corticosteroid therapy on lipid abnormalities in pediatric patients with systemic lupus erythematosus (SLE).Methods. Lipid measurements were obtained in an inception cohort of 139 pediatric patients with SLE (114 females). Fasting levels of total cholesterol, triglycerides, low-density lipoprotein (LDL) cholesterol, and highdensity lipoprotein (HDL) cholesterol in the SLE pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
2
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 42 publications
2
20
2
2
Order By: Relevance
“…A cohort study demonstrated an association between the use of CTCs and lipid profile changes in patients with juvenile SLE [27]. Another study verified that the prednisone dose affects the levels of LDL-c and total cholesterol independent of disease activity [33]. A possible explanation for the lack of an association between dyslipidemia and the use of medication in the present study may be due to the low doses of CTCs that were used.…”
Section: Discussioncontrasting
confidence: 51%
“…A cohort study demonstrated an association between the use of CTCs and lipid profile changes in patients with juvenile SLE [27]. Another study verified that the prednisone dose affects the levels of LDL-c and total cholesterol independent of disease activity [33]. A possible explanation for the lack of an association between dyslipidemia and the use of medication in the present study may be due to the low doses of CTCs that were used.…”
Section: Discussioncontrasting
confidence: 51%
“…10 Disease activity of SLE and lipid profile Dyslipoproteinemia of active disease consists of depressed HDL cholesterol with elevated very low density lipoprotein(VLDL) cholesterol and triglyceride (TG) levels. 11 Sarkissian T. et al study found that, active SLE patients had proatherogenic lipid profile 12 and also found that, at the time of diagnosis, the mean levels of total cholesterol, LDL cholesterol, and triglycerides were highest, whereas mean levels of HDL cholesterol were lowest. The percentage of patients with abnormal triglyceride value was highest at diagnosis, decreased at year one, and then remained relatively constant thereafter.…”
Section: Mechanisms Of Lipid Abnormalities In Slementioning
confidence: 92%
“…Low levels of HDL cholesterol were associated with active SLE, whereas the prednisolone dosage was associated with increased levels of HDL cholesterol. 12 The study done in our country found that control of disease activity in SLE was the most important factor in normalising the lipid profile.…”
Section: Mechanisms Of Lipid Abnormalities In Slementioning
confidence: 95%
See 1 more Smart Citation
“…Bekannt ist, dass die Arteriosklerose bereits im Kindesalter beginnt, die klinischen Zeichen aber erst viele Jahre später sichtbar werden. Arteriosklerotische Plaques und anomale Flussverhältnisse wurden bei jugendlichen SLE-Patienten bereits nach 2-5 Jahren nachgewiesen [23,25]. Die Ursache für das erhöhte Risiko liegt zum einen in der langdauernden Steroidtherapie, die zu Adipositas, arterieller Hypertonie, Hyperglykämie und Störung des Fettstoffwechsels führt, zum anderen prädispo-niert die Erkrankung selbst zur Arteriosklerose.…”
Section: Kardiopulmonale Beteiligungunclassified